The influence of the type of composition of PVA-chitosan blends on stability at elevated temperature - Robert Tylingo; Szymon Mania (Gdańsk University of Technology, 2020)
The dataset shows the results of a visual evaluation of chitosan and polyvinyl alcohol composites. The composites were prepared by combining chitosan water solutions, dissolved in selected acids, and polyvinyl alcohol solution, freeze drying, and heating at 150°C dry composites. The results confirm that the chitosan / PVA composites, in which the first polymer was dissolved with carbonic acid, are characterized by the highest thermal stability.